Peran Notaris Dalam Pembuatan Surat Keterangan Waris Terkait Penggolongan Penduduk Di Indonesia - Jeames Paschalix Tonggiroh (Faculty of Law Universitas Islam Indonesia, 2022)
The formulation of a Certificate of Inheritance based on population classification is contrary to the spirit of development in Indonesia which upholds democratic spirit, but there are cases where an heir who applies for a Certificate of Inheritance is rejected by a notary because the applicant's parents originate from two different groups. The formulation of the problem in this study is first, does a notary have a role in formulating a Certificate of Inheritance related to the classification of the population in Indonesia? Second, what is the role of a Notary in the making of a Certificate of Inheritance in regards to the fact that there remain population classifications in Indonesia? This is a normative legal research, the approaches used are statutory, conceptual and historical approaches. Data collection was carried out through library research and document studies which were then analyzed in a normative juridical manner. The results of the study concluded that first, the notary has a role in formulating a Certificate of Inheritance related to the classification of the population in Indonesia, namely as the only official who has the authority to make a deed as authentic evidence for heirs in the form of a Certificate of Inheritance without discriminating between ethnic groups, ethnicity or religion. Second, the role of the Notary in making the Certificate of Inheritance is related to the fact that there is still a population classification in Indonesia, namely as an official authorized to make a certificate of inheritance for Indonesian citizens of Chinese descent in accordance with Article 111 paragraph (1) of the Regulation of the State Minister of Agrarian Affairs/Head of the National Land Office Number 3 of 1997, due to legal political influence solely to fill the legal vacuum (rechtvacuum), hence after the issuance of Law Number 40 of 2008 on Racial and Ethnic Discrimination, the population classifications cease to exist.Key Word: Notary, Certificate of Inheritance, Population Classification AbstrakPembuatan Surat Keterangan Waris berdasarkan penggolongan penduduk bertentangan dengan semangat pembangunan negara Indonesia yang berjiwa demokrasi, namun terdapat kasus dimana seorang ahli waris yang hendak dibuatkan Surat Keterangan Waris ditolak oleh notaris karena orang tua dari pemohon berasal dari dua golongan yang berbeda. Rumusan masalah dalam penelitian ini adalah pertama, apakah Notaris mempunyai peran dalam pembuatan surat keterangan waris yang terkait dengan penggolongan penduduk di Indonesia? Kedua, bagaimana peran Notaris dalam pembuatan Surat Keterangan Waris terkait masih adanya penggolongan penduduk di Indonesia? Jenis penelitian ini menggunakan penelitian hukum normatif, pendekatan yang digunakan adalah pendekatan perundang-undangan, pendekatan konseptual dan pendekatan histori. Pengumpulan data dilakukan melalui studi Pustaka dan studi dokumen yang kemudian dianalisis secara yuridis normatif. Hasil penelitian menyimpulkan pertama, notaris mempunyai peran dalam pembuatan surat keterangan waris yang terkait dengan penggolongan penduduk di Indonesia yaitu sebagai satu-satunya pejabat yang memiliki kewenangan membuat akta sebagai bukti otentik bagi ahli waris dalam bentuk Surat Keterangan Waris tanpa membeda-bedakan golongan etnis, suku maupun agama. Kedua, peran Notaris dalam pembuatan Surat Keterangan Waris terkait masih adanya penggolongan penduduk di Indonesia yaitu sebagai pejabat yang berwenang membuat surat keterangan ahli waris bagi Warga Negara Indonesia keturunan Tionghua sesuai Pasal 111 ayat (1) Peraturan Menteri Negara Agraria/Kepala Kantor Pertanahan Nasional Nomor 3 tahun 1997, dikarenakan adanya pengaruh politik hukum yang semata-mata untuk mengisi kekosongan hukum (rechtvacuum), sehingga setelah terbitnya Undang-Undang Nomor 40 Tahun 2008 tentang Diskriminasi Ras dan Etnik maka penggolongan penduduk sudah tidak ada lagi.Kata-kata Kunci: Notaris, Surat Keterangan Waris, Penggolongan Penduduk